ANTIMICROBIAL RESISTANCE PATTERN AND PLASMID PROFILE OF SOME SALMONELLA SPP. ISOLATED FROM CLINICAL SAMPLES IN RIYADH AREA - Jaran, Adnan S. (European Scientific Journal, ESJ, 2015)
The aims of this work were to investigate the antimicrobial pattern and plasmid profile of different antibiotic resistant Salmonella species isolated from clinical samples and to find a possible relationship between resistance patterns and plasmid profile. Salmonella isolates were tested against 12 commonly used antimicrobial agents using the disc diffusion method to determine the resistance Patterns while plasmid DNA was extracted using Plasmid Miniprep method and separated by agarose gel electrophoresis. All strains Isolated were sensitive to Amoxicillin, Ciprofloxacin, Kanamycin and Amikacin. Isolated strains also showed resistance to Cotrimoxazole (20%), Erythromycin (90%), Ampicillin (90%), naladixic acid (30%), Cephalothin (13%), Tetracycline (60%), Gentamycin (4%) and Chloramphenicol (10%). Plasmid analysis of clinical isolates showed the presence of 1 to 5 plasmids with size range of 1.8 to 115 MDa. In conclusion, the number of antibiotics a Salmonella strain is resistant to may be directly related to the number of plasmids present in that strain. Therefore, recommended antimicrobials for the treatment of infections caused by Salmonella spp. should be based on a recent antibiogram tests.